Contributions to the aesthetics of St. Augustine - Warchał, Robert (Humaniora. Czasopismo Internetowe, 2023)
The following article aims to resolve the fundamental question referring to the way ideas exist in Augustine’s epistemology and also to familiarize the reader with contemporary interpretations of this issue. When framing his objectivist theory, Augustine drew on ancient traditions and the Bible, referring to deliberations on astronomy, cosmology and maths among others. In order for a work of art to be beautiful, it is necessary for human reason to perceive the right proportions in it, but their perfection does not depend solely on details and harmonious selection of parts, but also on something that links all these components to a mental idea. For Augustine, number is the principle of all things, but not in the sense of an arche, but in the sense of its presence in every being for example, the unity that the mind admires and of which it is itself an image. Its essence and meaning can only be found in God and therefore He is the first creator and greatest artist giving inspiration to all the arts. The thinker of Thagaste defined ideas as unalterable forms of things. In his view, all creation bears a certain trace of resemblance to God. That leads to a conclusion in the light of which every being is a greater or lesser implementation of the rules of res intelligibiles. The harmony of nature is of similar importance to him, as well as the beauty of the human body and mind. Facing the question of the ontological meaning of beauty author upholds its objectivity alongside other transcendental properties of being. Unity, equality, number, rhythm, proportion and order constitute the core elements of his aesthetics. The significance of Augustine’s doctrine lies in the fact that immaterial ideas enable achieving perfection in spiritual life, and hence bring us closer to the Creator.